2022
DOI: 10.1097/prs.0000000000009801
|View full text |Cite
|
Sign up to set email alerts
|

Traditional versus laterally extended upper blepharoplasty skin excisions: objective and patient reported outcomes

Abstract: Background: Different skin excision shapes may result in different aesthetic outcomes after upper blepharoplasty. Methods: Two skin-only excision shapes were evaluated objectively and subjectively in 28 matched patients with laterally extended skin excision (group A) or traditional elliptical skin excision (group B). The pretarsal show, lateral eyebrow height, amount of scarring (evaluated with the Patient and Observer Scar Assessment Scale), and patient-reported aesthetic results (evaluated using FACE-Q) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The literature investigating the influence of upper blepharoplasty surgery on brow height is almost entirely limited to retrospective studies with inconsistent findings. Seven studies reported statistically significant lowering of the brow position (Level 2 and Level 3), [16][17][18][19][20][21][22] while six other studies identified no significant change in brow height (Level 2 and Level 3). [23][24][25][26][27][28] While the inconsistency in the existing literature limits strong evidence-based recommendations for preoperative patient counseling when coexisting mild brow ptosis is also present, some conclusions can be drawn.…”
Section: Periorbital Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature investigating the influence of upper blepharoplasty surgery on brow height is almost entirely limited to retrospective studies with inconsistent findings. Seven studies reported statistically significant lowering of the brow position (Level 2 and Level 3), [16][17][18][19][20][21][22] while six other studies identified no significant change in brow height (Level 2 and Level 3). [23][24][25][26][27][28] While the inconsistency in the existing literature limits strong evidence-based recommendations for preoperative patient counseling when coexisting mild brow ptosis is also present, some conclusions can be drawn.…”
Section: Periorbital Examinationmentioning
confidence: 99%
“…Hollander et al compared the traditional method with a wide laterally extended upper blepharoplasty skin excision in a prospective comparative study (Level 3). 21 In comparison to the traditional design, the lateral extending skin excision began 5 to 6 mm above the medial canthus and curved superiorly, with the lateral portion positioned superiorly, spanning past the thin lid skin to reach the thick skin over the superolateral orbital rim. The lateral extension was positioned over and beyond the area of lateral hooding, placed at the height of the medial margin of the eyebrow (►Fig.…”
Section: Surgical Marking Designmentioning
confidence: 99%